Consumer attitudes and perceptions on consumption of edible insects among communities in western Kenya - Emmah Owidi; Gilbert Asoka; Eric Waga; Alfred Ochieng’; Fanuel Kawaka (PLoS ONE, 2025)
Edible insects are a highly sustainable and nutritional food source despite their low consumption in many communities. This study evaluated consumer attitudes and perceptions on consumption of edible insects in western Kenya. Eight focus group discussions (FGDs) were conducted in four rural and four urban markets in Kisumu and Vihiga counties. The FGDs were audio-recorded, transcribed, and analyzed using thematic content analysis. A total of 59 respondents consisting of 27 male and 32 females participated in the FGDs. The results showed higher acceptability and consumption of edible insects in rural areas compared to urban centers. The most popular edible insects were flying termites, grasshoppers, soldier termites and locusts. Consumption of these insects was mostly determined by their perceived high nutritional value, pleasant taste and familiarity as food sources. Seasonal capturing of the insects, especially during off-season also contributed to their low consumption. Respondents’ willingness to taste insect-based products was based on curiosity, packaging and familiarity with the product forms. These results suggest that there is need for interventions that promote public awareness and enhance the availability of edible insects and insect-based products, to support wider acceptability and consumption.